Hauwezi kuvuka ziwa hadi uwe na ujasiri wa kutouona urefu wa pwani: Made in Africa Evaluation as courageous conversation - Antony B. Maikuri; Vidhya Shanker; Rodney K. Hopson (African Evaluation Journal, 2022)
Background: The Kiswahili proverb that serves as the title of this article translates into English as, ‘You can never cross the ocean until you have the courage to lose sight of the shore’.